Investigating the Impacts of Mobile Assisted Reading on EFL Learners’ Vocabulary Knowledge Development - Mohammadreza Valizadeh (Sakarya University Journal of Education)
Abstract. In recent years, the proliferation of mobile technologies is transforming educational practices around the world. In this regard, students are attending classes with their mobile or tablet devices, on which they do most of their reading and writing activities. This has resulted in new understanding of literacy as being multimodal, fluid, sociocultural, and dynamic social practices. Meanwhile, mobile-assisted language learning developed exponentially, and its implementation has been reported to be generally effective in language education compared to traditional materials. Within this line of research, the current study examined the impacts of mobile assisted reading on English language learners’ vocabulary development. The participants of the research were 52 adult language learners divided into one experimental and one control groups. The participants in the experimental group employed mobile devices for reading a number of selected and simplified news reports, however, the control group used traditional print-based materials for reading the same content over the course of 10 weeks. The participants’ vocabulary gains were compared in pre- and post-tests and the findings indicated that the two groups improved their vocabulary knowledge, but the experimental group learned more vocabulary items and outperformed the control group on post-test. The findings highlighted the significant contribution of mobile phones in improving second language reading with associated impacts on vocabulary development. The study has implications for language teachers and materials development in teaching English to speakers of other languages.